Pakistan : Report on Observance of Standards and Codes-Fiscal Transparency Module-Update. (IMF Staff Country Reports; Country Report ;, 2004)
This paper presents an Update to the Report on the Observance of Standards and Codes on the Fiscal Transparency Module for Pakistan. Under the Project for Improvement of Financial Reporting and Auditing (PIFRA), key steps to enhance fiscal reporting and monitoring were taken recently. Accounting offices that process budget data are gradually being transformed to support the New Accounting Model and new information technology processes. Nineteen sites, including two core federal accounting offices, are now online. Data reconciliation issues are being addressed by fiscal monitoring committees operating both at the federal and provincial levels.